1986
DOI: 10.1056/nejm198605083141903
|View full text |Cite
|
Sign up to set email alerts
|

Silent Ischemia as a Marker for Early Unfavorable Outcomes in Patients with Unstable Angina

Abstract: We examined the prevalence and prognostic importance of silent myocardial ischemia detected by continuous electrocardiographic monitoring in 70 patients with unstable angina. All the patients received intensive medical treatment with nitrates, beta-blockers, and calcium-channel blockers. Continuous electrocardiographic recordings were made during the first two days in the coronary care unit to quantify the frequency and duration of asymptomatic ischemic episodes, defined as a transient ST-segment shift of 1 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
11

Year Published

1987
1987
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 656 publications
(121 citation statements)
references
References 36 publications
3
105
0
11
Order By: Relevance
“…Continuous Holter electrocardiographic monitoring was performed for 72 hr from the time of entry into the study (including the preinfusion observation period). Analysis of Holter ST segment data was performed according to methods previously described by Gottlieb et al 13 Venous blood samples for routine hematologic serum chemistry, and hemostasis analysis were drawn before treatment and during the infusion. Blood samples for hemostasis analysis were drawn on 0.O1M citrate and 200 kIU aprotinin/ml of blood at 1, 5, and 12 hr after the beginning of the infusion.…”
Section: Methodsmentioning
confidence: 99%
“…Continuous Holter electrocardiographic monitoring was performed for 72 hr from the time of entry into the study (including the preinfusion observation period). Analysis of Holter ST segment data was performed according to methods previously described by Gottlieb et al 13 Venous blood samples for routine hematologic serum chemistry, and hemostasis analysis were drawn before treatment and during the infusion. Blood samples for hemostasis analysis were drawn on 0.O1M citrate and 200 kIU aprotinin/ml of blood at 1, 5, and 12 hr after the beginning of the infusion.…”
Section: Methodsmentioning
confidence: 99%
“…[41][42][43][44][45] The 3-to 5-fold increase in risk of death, infarction, and revascularization has been shown to continue out to 1-and 2-year follow-up. 40,46 Transient ischemia, much of which is silent, is also detectible during Holter monitoring in the acute phase after MI, and in this setting it is associated with an adverse "in-hospital" and medium-term prognosis in terms of death and reinfarction in addition to combined end points including revascularization and angina [47][48][49][50][51][52][53][54][55][56] (Table 1).…”
Section: Cohn Et Al Silent Myocardial Ischemiamentioning
confidence: 99%
“…ST-segment monitoring stud-ies of patients hospitalized with unstable angina show that although 80% to 90% of transient ischemic events are asymptomatic, they are nonetheless significant markers for unfavorable short-and long-term outcomes (Table 2). [63][64][65][66][67][68][69][70] Patients Who Present to the ED With Chest Pain or Anginal Equivalent Symptoms It is not uncommon for patients with acute ST-elevation MI to have an initial ECG that is nondiagnostic for acute ischemia. Investigators who use continuous monitoring have shown that the ST segment often is dynamic in the early hours of acute MI.…”
Section: Patients In the Early Phase Of Acute Coronary Syndromes (St-mentioning
confidence: 99%